Haptoglobin 1-1 Genotype Modulates the Association of Glycemic Control With Hippocampal Volume in Elderly Individuals With Type 2 Diabetes - Livny, Abigail (Diabetes, 2017)
Recent evidence suggests that glycemic control is associated with cognitive function in older patients with type 2 diabetes who are carriers of the haptoglobin (Hp) 1-1 genotype compared with noncarriers. We assessed whether poor glycemic control in Hp 1-1 carriers is more strongly associated with smaller hippocampal volume than in noncarriers. Hippocampal volume was generated from high-resolution structural T1 MRI obtained for 224 participants (28 Hp 1-1 carriers [12.5%] and 196 noncarriers [87.5%]) from the Israel Diabetes and Cognitive Decline (IDCD) study, who had a mean (SD) number of years in the Maccabi Healthcare Services (MHS) registry of 8.35 (2.63) and a mean (SD) HbA(1c) level of 6.66 (0.73)% [49 mmol/mol]. A stronger negative association between right hippocampal volume and HbA(1c) was found in patients with the Hp 1-1 genotype, with a 0.032-mL decrease in right hippocampal volume per 14% increase in HbA(1c) (P = 0.0007) versus a 0.009-mL decrease in Hp 1-1 noncarriers (P = 0.047), after adjusting for total intracranial volume, age, sex, follow-up years in the registry, and cardiovascular factor (interaction, P = 0.025). This indicates that 29.66% of the total variance in right hippocampal volume is explained by HbA(1c) levels among Hp 1-1 carriers and that 3.22% is explained by HbA(1c) levels among Hp 1-1 noncarriers. Our results suggest that the hippocampus of Hp 1-1 carriers may be more vulnerable to the insults of poor glycemic control.